1986
DOI: 10.1148/radiology.158.1.2416006
|View full text |Cite
|
Sign up to set email alerts
|

Biliary decompression: an institutional comparison of percutaneous and endoscopic methods.

Abstract: Endoscopically performed biliary drainage (EPBD) is now an alternative to percutaneous biliary drainage. The morbidity, mortality, and survival statistics of 97 patients with obstructive jaundice who had undergone percutaneous transhepatic biliary drainage (PTBD) and surgery, PTBD alone, EPBD and surgery, or EPBD alone were compared. Overall, the EPBD group had fewer complications and lower mortality than the other groups. When palliative treatment of patients with malignancies was compared, the complication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
8
0
5
Order By: Relevance
“…It was reported that the technical success rate of PTBD ranges from 75% to 100%, its clinical success rate ranges from 65% to 92%, and its complication rate ranges from 9% to 31%. [61][62][63][64] The average complication rate of the combined data for each EUS-guided drainage procedure in our review was not higher than that of the papers for PTBD in the past 2 decades. In recent years, many papers have reported on EUS-guided drainage as an alternative procedure to PTBD.…”
Section: Ptbd Versus Eus-bdmentioning
confidence: 95%
“…It was reported that the technical success rate of PTBD ranges from 75% to 100%, its clinical success rate ranges from 65% to 92%, and its complication rate ranges from 9% to 31%. [61][62][63][64] The average complication rate of the combined data for each EUS-guided drainage procedure in our review was not higher than that of the papers for PTBD in the past 2 decades. In recent years, many papers have reported on EUS-guided drainage as an alternative procedure to PTBD.…”
Section: Ptbd Versus Eus-bdmentioning
confidence: 95%
“…Table 3 summarizes the data [28,[92][93][94][95]. It is generally perceived that trans-hepatic drainage carries a higher risk of morbidity than does endoscopic drainage, with four of the five studies reviewed demonstrating this, although only one study by Speer et al found this difference to be statistically significant.…”
Section: Endoscopic Placement Versus Percutaneous Placement Of Stentsmentioning
confidence: 99%
“…Up to now, in most of the centers where both techniques are applicable, the endoscopic route is regarded as the first choice, while transhepatic access is used in case of endoscopic failure or inapplicability [12,13].…”
Section: Biliary Obstruction and Jaundicementioning
confidence: 99%